Handbook of Statistical Genetics 2003
DOI: 10.1002/0470022620.bbc19
|View full text |Cite
|
Sign up to set email alerts
|

Marker‐Assisted Selection and Introgression

Abstract: Good maps of molecular markers now exist for many species. In this chapter we discuss the statistical methodology that has been developed to facilitate the exploitation of these maps in commercial breeding programs. Methods appropriate both for populations derived from inbred line crosses and outbred populations, particularly dairy cattle populations, are considered, and the possible utility of such methods discussed. There is a consensus that incorporating marker information into breeding programs can increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…BACKCROSSING AND GENETIC IMPROVEMENT (a) Optimization of marker-assisted backcrossing In addition to conventional breeding methods, various aspects of the use of molecular markers (for controlling the target genes, accelerating the recovery of recurrent genome or reducing linkage drag) to improve the efficiency of introgression in backcross breeding programmes have been investigated from a theoretical standpoint in recent years. These were reviewed recently Whittaker 2001;Dekkers & Hospital 2002;Hospital 2003) and will not be detailed here. Whether it is called marker-assisted introgression or marker-assisted backcross, use of markers in backcross breeding programmes is efficient.…”
Section: Introductionmentioning
confidence: 99%
“…BACKCROSSING AND GENETIC IMPROVEMENT (a) Optimization of marker-assisted backcrossing In addition to conventional breeding methods, various aspects of the use of molecular markers (for controlling the target genes, accelerating the recovery of recurrent genome or reducing linkage drag) to improve the efficiency of introgression in backcross breeding programmes have been investigated from a theoretical standpoint in recent years. These were reviewed recently Whittaker 2001;Dekkers & Hospital 2002;Hospital 2003) and will not be detailed here. Whether it is called marker-assisted introgression or marker-assisted backcross, use of markers in backcross breeding programmes is efficient.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, as illustrated in this study, the skewed t prior distribution proposed offers flexibility and robustness concerning the distribution of genetic effects associated with molecular markers. The use of shrinkage as suggested by Whittaker (2001) and Lange & Whittaker (2001), and generalized into a Bayesian setting by Gianola et al (2003), avoids problems due to overparameterization, and colinearity causing unstable least-squares estimates. The skewed t-distribution retains the desirable properties described in Gianola et al (2003) but also makes it possible to describe differences between lines in an F 2 cross more adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Recent development of molecular techniques has provided a massive number of molecular markers and, as a consequence, dense genetic maps are now available for a number of species. An obvious use of this molecular information is for markerassisted selection in livestock and plant populations (Whittaker, 2001). The basic idea of markerassisted selection is to detect and exploit linkage disequilibrium between mutations that cause genetic variations and presumably neutral molecular markers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, unless all QTL affecting the traits of interest can be identified, phenotypic values should be combined with the marker scores to increase LMSI efficiency (Dekkers and Settar 2004). Moreau et al (2000) and Whittaker (2003) found that the LMSI is more effective than LPSI only in early generation testing and that LMSI increased costs because of molecular marker evaluation. The LMSI assumes that favorable alleles are known, as are their average effects on phenotype (Lande and Thompson 1990;Hospital et al 1997).…”
Section: Linear Marker Selection Indicesmentioning
confidence: 99%